Digital Liquid Patterning: A Versatile Method for Maskless Generation of Liquid Patterns and Gradients. Issue 2 (5th February 2014) - Efremov, Alexander N.; Grunze, Michael; Levkin, Pavel A.
<x xml:space="preserve">Abstract</x> A facile, maskless, digital liquid patterning method, allowing on‐demand fabrication of liquid patterns without the need to change the substrate or use different photomasks, is described. Patterns with customized geometries can be created manually by simple pipetting. An application of this maskless method to create patterns of particles, cells, hydrogels, and complex liquid gradients compatible with cell studies is shown. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>